Perspectiva de tiempo futuro y satisfacción con la vida en adolescentes: un estudio transcultural, (dedicado al Prof. Dr. Willy Lens): Future time perspective and life satisfaction in adolescents and youngsters: a cross cultural study (devoted to the memory of Prof. Dr. Willy Lens) - Dora Herrera, Lennia Matos, Patricia Martínez- Willy Lens (Revista de Orientación Educacional, 2019)
El presente artículo se sustenta en una investigación trans-cultural que describe la relación entre las variables Perspectiva de Tiempo Futuro (PTF) y satisfacción con la vida. Para desarrollar el estudio se evaluó 648 estudiantes universitarios de tres países del continente americano: Costa Rica (n=202); Perú (n=217) y Estados Unidos (n=229). El modelo original de investigación consideró múltiples variables relacionadas con la satisfacción de vida. Para el presente artículo, se presenta únicamente la asociación entre PTF (contenido de metas) y satisfacción con la vida. Cabe señalar que la longitud de la Perspectiva de Tiempo Futuro fue mayor en Perú que en los otros países analizados. Se considera relevante profundizar en esta línea de investigación a fin de establecer nuevas inferencias científicas. Abstract: This is a cross cultural research in which the relationship between Future Time Perspective (FTP) and life satisfaction in adolescents is described. 648 university students from three American countries were assessed: Costa Rica (n=202); Peru (n=217) and the United States (n=229). The original research model considers different variables associated to life satisfaction. For this manuscript we present the association between FTP content categories and life satisfaction. Using the whole model, predictors of life satisfaction were diverse (FTP, perceived stress, coping resources patterns of perfectionism and life satisfaction) in different countries but we can affirm that, wellbeing was positively associated to planning, time management or goal and priorities setting. Length of FTP was larger in Peru than in other countries. Future research in this line of investigation should work deeply for stronger cross-cultural conclusions.